Design Ultra-Wideband Antenna have A Band Rejection Desired to Avoid Interference from Existing Bands - Ansam Qasim Kamil; ِAli Khalid Jassim (Bulletin of Electrical Engineering and Informatics, 2022)
Ultra-wideband antenna with band notch for rejecting bands. Rectangular slots are introduced on an arborescent patch to get UWB, coverage from 3.1–10.6 GHz. The antenna structure is fancied on FR4 the substrate with a size of 24 mm×24 mm×1.6 mm, a band notch located at 4.7 GHz is generated by adding the rectangular slot on the patch this microstrip antenna is simulated by computer simulation technology, the simulated and manufactured results show the antenna for wireless communication,to reduce the problem of interference in bands in communication systems by using the current distribution techniques, large bandwidths are reduced and unwanted bands are rejected by inserting notch such as rectangular slit and side slot on the patch. The presented antenna, use current redistribution technology, for the antenna designed by adding a rectangular aperture on a rectangular patch to change the current path to a zero value. Despite the fact that these antennas have strong band-notch characteristics and can match the criteria of UWB communication applications.